Dualistyczna koncepcja prawa prywatnego a umowy handlowe — uwagi na przykładzie umowy komisu - Wójtowicz, Ewa (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Currently commercial contracts are not a normative category, unlike under the regulations of the Commercial Code. However, they are distinguished in the doctrine of civil law. The consignment contract as a commercial contract is regulated in the Civil Code in accordance with the concept of monism of private law. A return to dualism would require taking into account the current state oftrade, its diversity, and the existence of consumer contracts.
Keywords: entrepreneur; commercial law; consignment agreement; Commercial Code; commercial contracts